Corporate debt maturity and investment over the business cycle - Johannes Poeschl (Danmarks Nationalbank, 2017)
I study the business cycle dynamics of the maturity structure of the debt of U.S. non-financial firms. I document three facts: First, the aggregate share of long-term debt in total debt is pro-cyclical. Second, the long-term debt share of small firms has a higher standard deviation and correlation with output than the long-term debt share of large firms. Third, large firms tend to use a larger share of long-term debt in general. To account for these facts, I construct a quantitative dynamic equilibrium model in which firms optimally choose investment, leverage, debt maturity, dividends, and default, subject to idiosyncratic and aggregate risk. When they choose their debt maturity, firms trade off default premia and rollover costs. As a result, financially constrained firms endogenously prefer to issue short-term debt, because they face high default premia on long-term debt. Financially unconstrained firms issue long-term debt, because it has lower rollover costs. The model, which is parameterized to match cross-sectional moments, can match stylized facts about the level and dynamics of the maturity structure of debt, both in the aggregate and along the firm size distribution.
Keywords: E32; E44; G32; G33; 330; Financial stability; Business enterprises and households; Models